The Faculty of Sensing - Thinking with, through, and by Anton Wilhelm Amo - Amo, Anton Wilhelm; Hillgärtner, Jule; Kaczmarek, Nele; Soh Bejeng Ndikung, Bonaventure; Kunstverein Braunschweig, Braunschweig (Milan : Mousse Publishing, 2021)
artists: Majewski, Antje ; Guesselé-Garai, Olivier ; Dasovic, Anna ; Okpu-Egbe, Adjani ; Kaersenhout, Patricia ; Akoi-Jackson, Bernard ; Cqunta, Lungiswa ; Eshetu, Theo ; Désert, Jean-Ulrick ; Majewski, Antje ; Fawundu, Adama Delphine ; Akinbiyi, Akinbode ; Lelliott, Kitso Lynn ; Martinez Garay, Claudia ; Resolve Collective ; Wolf, Konrad ; andcompany&Co
Texts by Justin E. H. Smith, Jule Hillgärtner, Paulin J. Hountondji, Nele Kaczmarek, Seloua Luste Boulbina, Jota Mombaça, Peggy Piesche, Bonaventure Soh Bejeng Ndikung, and Victor U. Emma-Adamah
The Faculty of Sensing – Thinking With, Through, and by Anton Wilhelm Amo describes an artistic and scholarly inquiry into the work of Anton Wilhelm Amo (c. 1700–after 1753), an outstanding philosopher of the early eighteenth-century Enlightenment. The volume brings together international voices from the areas of philosophy, poetry, science, and art; each evokes Amo's writings and their reception in a discussion on the highly topical politics of referentiality, erasure, and decolonization. The research and the exhibition project includes newly-developed works by sixteen artists, which were presented at Kunstverein Braunschweig and at SAVVY Contemporary, Berlin, in 2020–21. (provided by publisher)
This publication has been published on the occasion of the research and exhibition project 'The Faculty of Sensing - Thinking With, Throug, and by Anton Wilhelm Amo' at Kunstverein Braunschweig, March 28 to September 13, 2020
boek